Mitochondrial Peroxiredoxin III Protects against Non-Alcoholic Fatty Liver Disease Caused by a Methionine-Choline Deficient Diet - Jiyoung Park; Nam Hee Kim; Ho Jin Yi; Sue Goo Rhee; Hyun Ae Woo (MDPI AG, 2022)
Non-alcoholic fatty liver disease (NAFLD) is emerging as the most common chronic liver disease worldwide. In addition, NAFLD may increase the risk of cardiovascular and liver-related diseases, and displays features of metabolic syndrome. In NAFLD, oxidative stress is primarily caused by excessive free fatty acids. The oxidation of fatty acids is usually caused by β-oxidation of mitochondria under normal conditions, resulting in the production of energy. However, when the inflow of fatty acids in NAFLD becomes excessive, the β-oxidation of mitochondria becomes saturated and the oxidation process increases at sites including peroxisomes and microsomes, thereby increasing production of reactive oxygen species (ROS). Thus, hepatic mitochondrial ROS play an important role in the pathogenesis of NAFLD. Eliminating mitochondrial ROS may improve NAFLD, but the underlying mechanism remains unclear. We examined the effect of mitochondrial ROS on NAFLD by focusing on peroxiredoxin (Prx), an antioxidant protein that can remove hydrogen peroxide. The protective effect and pathological phenomenon of mitochondrial peroxiredoxin in methionine-choline deficient diet (MCD)-induced liver injury was assessed in a mouse model of NAFLD. In these mice, mitochondrial peroxiredoxin deficiency significantly increased hepatic steatosis and fibrosis. In addition, ablation of Prx III enhances susceptibility to MCD diet-induced oxidative stress and exacerbates NAFLD progression by promoting inflammation. The binding assay results also showed that Prx III-deficient mice had more severe liver damage than Prx III-abundant mice in MCD diet liver injury models. The present data suggest that mitochondrial peroxiredoxin III could be a therapeutic target for preventing and suppressing diet-induced NAFLD.